2020
DOI: 10.4244/eij-d-19-00797
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of transcaval transcatheter aortic valve implantation: a multicentre European registry

Abstract: Aims: A transfemoral transarterial approach is considered the preferable access route for transcatheter aortic valve implantation (TAVI), followed by a transaxillary/subclavian TAVI approach. However, these approaches may not be an option in all patients. This study aimed to report the initial European experience with transfemoral transcaval TAVI.Methods and results: Data on 50 patients treated by transcaval TAVI in five European centres were collected and analysed according to the Valve Academic Research Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…At 12 months, there were no postdischarge vascular complications despite universal implantation of permeable vascular nitinol occluders. 11 Results were similar in an early European 12 and Israeli 13 reports.…”
Section: Clinical Applicationssupporting
confidence: 74%
“…At 12 months, there were no postdischarge vascular complications despite universal implantation of permeable vascular nitinol occluders. 11 Results were similar in an early European 12 and Israeli 13 reports.…”
Section: Clinical Applicationssupporting
confidence: 74%
“…In this case report, we describe the step-by-step procedural guidance. Based on our previous experiences, 3,6 we concluded that a good anatomical selection, precise cava-aorta puncture, and complete shunt occlusion contribute to the success of the transcaval procedure.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown the feasibility and safety of transcaval TAVI. [3][4][5] Additionally, transcaval TAVI requires a similar setting in the operation room as transfemoral TAVI with good radiation protection and without the change of operators' positions. In this case report, we describe the step-by-step procedural guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The third nFP access for TAVR not addressed in these two papers is the transcarotid (TC) access. Surprisingly, the authors of the first paper 9 proposed the transcaval approach to their patients not suitable for either the transfemoral or axillary approach and did not first consider the TC approach. The TC-TAVR approach (Figure 1) represented 3.4% of patients treated with TAVR in the FRANCE TAVI registry 2 .…”
Section: Article See Page 1325mentioning
confidence: 99%
“…In this issue of EuroIntervention, two papers 9,10 report the results of two alternative nFP access routes for TAVR procedures. The first paper by Costa et al 9 reports the initial European experience of transcaval TAVR.…”
mentioning
confidence: 99%